2014
DOI: 10.1111/sjos.12105
|View full text |Cite
|
Sign up to set email alerts
|

A Central Limit Theorem in Non‐parametric Regression with Truncated, Censored and Dependent Data

Abstract: On the basis of the idea of the Nadaraya–Watson (NW) kernel smoother and the technique of the local linear (LL) smoother, we construct the NW and LL estimators of conditional mean functions and their derivatives for a left‐truncated and right‐censored model. The target function includes the regression function, the conditional moment and the conditional distribution function as special cases. It is assumed that the lifetime observations with covariates form a stationary α‐mixing sequence. Asymptotic normality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The estimators m N W (x) and m LL (x) are constructed for the first time in Liang et al (2015), who investigated the asymptotic normality of m N W (x) and m LL (x) under dependent assumptions.…”
Section: Remark 22mentioning
confidence: 99%
See 4 more Smart Citations
“…The estimators m N W (x) and m LL (x) are constructed for the first time in Liang et al (2015), who investigated the asymptotic normality of m N W (x) and m LL (x) under dependent assumptions.…”
Section: Remark 22mentioning
confidence: 99%
“…In this section, we conduce a simulated study to investigate In order to obtain an α-mixing observed sequence {X i , Z i , T i , δ i }, we generate the data as in the simulated study by Liang et al (2015), which is as follows.…”
Section: Simulation Studymentioning
confidence: 99%
See 3 more Smart Citations